DNA repair capacity and response to treatment of colon cancer - Vodicka, Pavel; Vodenkova, Sona; Buchler, Tomas; Vodickova, Ludmila (Pharmacogenomics, 2019)
DNA repair, a complex biological process, ensures genomic integrity. Alterations in DNA repair, occurring in many cancers, contribute to the accumulation of mutations in the genome, resulting in genomic instability and cancer progression. DNA repair also plays a substantial role in response to chemotherapeutics: rapidly dividing colon cancer cells, vulnerable to DNA-damaging agents and overcoming DNA repair, undergo cell death. DNA repair capacity represents a complex biomarker, integrating gene variants, gene expressions, the stability of gene products, the effect of inhibitors/stimulators, lifestyle and environmental factors. Here, we discuss DNA repair capacity in sporadic colon cancer, a frequent malignancy worldwide, in relation to tumor heterogeneity, prognosis and prediction, measurements in surrogate and target tissues and suggest important tasks to be addressed.
Keywords: buněčná smrt; prediction of therapy response; DNA Damage; prognosis; epigeneze genetická; nestabilita genomu; Prognosis; regulace genové exprese u nádorů; Epigenesis, Genetic; poškození DNA; DNA repair capacity; mutace; Cell Death; nádory tračníku; prognóza; DNA repair; Mutation; Humans; Gene Expression Regulation, Neoplastic; oprava DNA; Colonic Neoplasms; Genomic Instability; DNA Repair; colon cancer; lidé